Governing Citizens Through Waste: A Case of the J-Sampah Juang Digital Platform in Jember - Sukron Makmun; Suji suji; Supranoto Supranoto; Hasyisy Ahmad; Fitrah Abdi Shandy (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2026)
This study explores the practice of digital waste governance in Jember Regency, Indonesia, through a Foucauldian lens of governmentality. Using the J-Sampah Juang application as a case study, the research examines how digital technologies are employed by local governments not merely to manage waste, but to shape citizen behavior and environmental subjectivity. Drawing on Michel Foucault's concept of governmentality, which encompasses the art of governing beyond the state through rationalities, techniques, and technologies, this study examines how the J-Sampah Juang app functions as an instrument of subtle control, promoting self-discipline, environmental responsibility, and citizen participation. This research employs a qualitative case study approach to investigate how the J-Sampah Juang application functions as a tool of digital governmentality in the context of local waste governance in Jember Regency, Indonesia. The case study method is employed to gain an in-depth understanding of the social, political, and technological dynamics underlying the application's implementation. Data collection was conducted through in-depth interviews, participant observation, and document analysis. The data were analyzed using a thematic analysis guided by Foucauldian concepts, including governmentality, technologies of the self, discipline, and subjectification. The findings suggest that the application functions as a form of technological governance, embedding mechanisms of surveillance, rewards, and behavioral nudging. These features reconfigure the relationship between state and citizen, shifting from command-based governance to conduct-based regulation, where individuals become active agents in managing themselves and their communities. While the platform improves administrative efficiency and public participation, it also raises critical questions about inclusion, equity, and the hidden dimensions of power in digital governance.  Keywords:  Governmentality;  waste; digital platform; digital inclusion; J-Sampah Juang